2016
DOI: 10.1089/lap.2015.0494
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colorectal Resection in Patients with Sarcopenia: A Retrospective Case-Control Study

Abstract: Laparoscopic colorectal resection was feasible in patients with sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…As shown in the study by Tegels [34], the incidence of sarcopenia is higher in patients with gastric cancer, but it is not associated with a poor postoperative prognosis. According to Ouchi [36], sarcopenia does not increase the incidence of total and severe postoperative complications in patients with colorectal cancer [36]. In the present study, signi cant differences in the incidences of total postoperative complications, surgical complications and systemic complications were not observed between the patients with g-NENs presenting with and without sarcopenia.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…As shown in the study by Tegels [34], the incidence of sarcopenia is higher in patients with gastric cancer, but it is not associated with a poor postoperative prognosis. According to Ouchi [36], sarcopenia does not increase the incidence of total and severe postoperative complications in patients with colorectal cancer [36]. In the present study, signi cant differences in the incidences of total postoperative complications, surgical complications and systemic complications were not observed between the patients with g-NENs presenting with and without sarcopenia.…”
Section: Discussionsupporting
confidence: 42%
“…An American study identi ed an association between sarcopenia and the short-term outcomes in patients with pancreatic cancer after pancreatectomy [35]. However, some studies have reported the opposite results [34,36]. As shown in the study by Tegels [34], the incidence of sarcopenia is higher in patients with gastric cancer, but it is not associated with a poor postoperative prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the study by Tegels [34], the incidence of sarcopenia is higher in patients with gastric cancer, but it is not associated with a poor postoperative prognosis. According to Ouchi [36], sarcopenia does not increase the incidence of total and severe postoperative complications in patients with colorectal cancer [36]. In the present study, significant differences in the incidences of total postoperative complications, surgical complications and systemic complications were not observed between the patients with g-NENs presenting with and without sarcopenia.…”
Section: Discussionsupporting
confidence: 41%
“…An American study identified an association between sarcopenia and the short-term outcomes in patients with pancreatic cancer after pancreatectomy [35]. However, some studies have reported the opposite results [34,36]. As shown in the study by Tegels [34], the incidence of sarcopenia is higher in patients with gastric cancer, but it is not associated with a poor postoperative prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…GMANEC is de ned as a malignant tumor with morphological components of glandular epithelial cells and neuroendocrine cells, both of which account for at least more than 30% [4]. Previous studies have shown that the clinical characteristics of gMANEC largely depend on the proportion of neuroendocrine carcinoma components [36,37]. Fernandes et al believe that the prognosis of gMANEC might be related to whether certain tumor components are more invasive [38].…”
Section: Discussionmentioning
confidence: 99%